Cytokeratin 5–Positive Cells Represent a Therapy Resistant subpopulation in Epithelial Ovarian Cancer. Issue 9 (November 2015) - Corr, Bradley R.; Finlay-Schultz, Jessica; Rosen, Rachel B.; Qamar, Lubna; Post, Miriam D.; Behbakht, Kian; Spillman, Monique A.; Sartorius, Carol A.
Abstract : Objective: Cytokeratin 5 (CK5) is an epithelial cell marker implicated in stem and progenitor cell activity in glandular reproductive tissues and endocrine and chemotherapy resistance in estrogen receptor (ER) + breast cancer. The goal of this study was to determine the prevalence of CK5 expression in ovarian cancer and the response of CK5 + cell populations to cisplatin therapy. Materials and Methods: Cytokeratin 5 expression was evaluated in 2 ovarian tissue microarrays, representing 137 neoplasms, and 6 ovarian cancer cell lines. Cell lines were treated with IC50 (half-maximal inhibitory concentration) cisplatin, and the prevalence of CK5 + cells pretreatment and posttreatment was determined. Proliferation of CK5 + versus CK5 − cell populations was determined using 5-bromo-2′-deoxyuridine incorporation. Chemotherapy-induced apoptosis in CK5 + versus CK5 − cells was measured using immunohistochemical staining for cleaved caspase-3. Results: Cytokeratin 5 was expressed in 39.3% (42 of 107) of epithelial ovarian cancers with a range of 1% to 80% positive cells. Serous and endometrioid histologic subtypes had the highest percentage of CK5 + specimens. Cytokeratin 5 expression correlated with ER positivity (38 of 42 CK5 + tumors were also ER + ). Cytokeratin 5 was expressed in 5 of 6 overall and 4 of 4 ER + epithelial ovarian cancer cell lines ranging from 2.4% to 52.7% positive cells. Cytokeratin 5 + compared with CK5 − cells were slower proliferating. The prevalence of CK5 + cells increased after 48-hour cisplatin treatment in 4 of 5 cell lines tested. Cytokeratin 5 + ovarian cancer cells compared with CK5 − ovarian cancer cells were more resistant to cisplatin-induced apoptosis. Conclusions: Cytokeratin 5 is expressed in a significant proportion of epithelial ovarian cancers and represents a slower proliferating chemoresistant subpopulation that may warrant cotargeting in combination therapy. Abstract : Supplemental digital content is available in the text.